EMOSI NEGATIF SISWA KELAS XI SMAN 1 SUNGAI LIMAU - yuliani, risa (Konselor, 2013)
Changes in behavior and emotional control in adolescents, the increasing age of the students are expected to control their negative emotions. The reality on the ground is still there are students who have not been able to control negative emotions such as irritability well if not in accordance with what they want, fear of not able to complete the tasks set by the teacher. This study aimed to describe negative emotions student population of 304 students, a sample of 75 students, using a random sampling technique. The results showed that negative emotions of students is high.Keywords: Negative Emotions; Students